The Cell Wall and Membrane of Cryptococcus neoformans Possess a Mitogen for Human T Lymphocytes - Mody, Christopher H. (American Society for Microbiology, 1999)
The mechanism of human T-lymphocyte activation by the pathogenic yeast Cryptococcus neoformans has not been established. Previous investigations have suggested that C. neoformans contains a mitogen for T lymphocytes, while other investigators have attributed lymphocyte proliferation in vitro to a recall antigen. Because of the potential importance of the mechanism of T-cell activation for our understanding of the immune response to C. neoformans, the present studies were performed to determine whether C. neoformans contains a mitogen for T lymphocytes. C. neoformans stimulates fetal blood lymphocytes to proliferate and stimulates proliferation of CD45RA(+) cells from adults, indicating that it stimulates naive T cells. The T-cell response to C. neoformans was dependent upon the presence of accessory cells. However, allogeneic cells were sufficient for accessory cell function, indicating that the response was not major histocompatibility complex restricted. The percentage of T cells in the cell cycle was higher than that with the recall antigen tetanus toxoid but lower than that with the mitogenic lectin phytohemagglutinin A or the superantigen Staphylococcus enterotoxin B. Precursor frequency analysis established that 1 in 7,750 ± 2,270 T cells proliferated in response to the cryptococcal cell wall and membrane. Compared to the case for most mitogens or superantigens, the proliferative response is late and the number of T cells that enter the cell cycle and the precursor frequency are low, indicating that the mitogenic effect is modest. However, the mitogenic effect of C. neoformans should be considered when interpreting the immune response to C. neoformans, since even weak mitogens can have profound effects on host defense.